The effect of human resource development and leadership on employee performance with organizational commitment - Sabri Sabri; Sumardin Sumardin; Haji Mustaqim (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Employee development greatly affects the development of the organization. Professionally developed employees can bring various benefits to the organization. This study aims to analyze the influence of human resource development and leadership on employee performance with organizational commitment as a moderation variable in Batamindo Industrial Park companies. Human resource development aims to increase employee knowledge in terms of knowledge and practice skills through education, training, non-training and learning tasks. Furthermore, employee performance is the quality of work results, quantity of work, attendance and teamwork ability. This study uses a qualitative approach with a correlational associative research method by distributing questionnaires to employees June-July 2023 using a google form. The research sample was taken by purposive sampling involving 100 respondents. Data analysis was carried out using multiple regression analysis and data was processed using Smart PLS 3. The results of this study show that leadership variables and organizational commitment have a significant effect on employee performance. Human resource development does not have a significant effect on employee performance, this is due to HR development that is not implemented properly or without a mature plan so that it does not have a significant impact. Poor execution and lack of support from management. Organizational commitment is proven to be able to strengthen the influence of leadership and human resource development on employee performance.